2015
DOI: 10.1097/md.0000000000001319
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Supplementation in Intensive Care Patients

Abstract: The role of glutamine (GLN) supplementation in critically ill patients is controversial. Our aim was to analyze its potential effect in patients admitted to intensive care unit (ICU).We performed a systematic literature review through Medline, Embase, Pubmed, Scopus, Ovid, ISI Web of Science, and the Cochrane-Controlled Trials Register searching for randomized clinical trials (RCTs) published from 1983 to 2014 and comparing GLN supplementation to no supplementation in patients admitted to ICU. A random-effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 63 publications
2
11
0
1
Order By: Relevance
“…However, in subgroup analyses, infectious morbidity was reduced in patients receiving parenteral glutamine, for more than five days and with less severe disease. The authors speculated that glutamine does not have a protective effect on mortality in the most severe patients, since glutamine supplementation is not sufficient for recovery of organ dysfunction, which is the main determinant of death in these cases [ 12 ]. In contrast, the “GLND” trial, a prospective, randomized, controlled, double-blind, multicenter, phase III study that investigated the safety and clinical efficacy of glutamine dipeptide-supplemented parenteral nutrition showed that glutamine supplementation is safe, but did not improve clinical outcomes, as well as hospital infections, in surgical ICU patients after gastrointestinal, vascular, or cardiac surgery.…”
Section: Glutamine Therapy In Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in subgroup analyses, infectious morbidity was reduced in patients receiving parenteral glutamine, for more than five days and with less severe disease. The authors speculated that glutamine does not have a protective effect on mortality in the most severe patients, since glutamine supplementation is not sufficient for recovery of organ dysfunction, which is the main determinant of death in these cases [ 12 ]. In contrast, the “GLND” trial, a prospective, randomized, controlled, double-blind, multicenter, phase III study that investigated the safety and clinical efficacy of glutamine dipeptide-supplemented parenteral nutrition showed that glutamine supplementation is safe, but did not improve clinical outcomes, as well as hospital infections, in surgical ICU patients after gastrointestinal, vascular, or cardiac surgery.…”
Section: Glutamine Therapy In Respiratory Diseasesmentioning
confidence: 99%
“…Compared to an isonitrogenous control, enteral glutamine had no impact on outcomes in this general population of ICU patients, but reduced in-hospital mortality in burn patients [ 11 ]. In a systematic review and meta-analysis including clinical trials of patients admitted to ICU that used both parenteral and enteral glutamine, supplementation was not found to reduce in-hospital mortality, ICU mortality, or the rate of infection [ 12 ]. Thus, the effect of glutamine appears to depend on the route of administration, and parenteral supplementation may lead to better results.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine deficiency contributes to the dysfunction of the immune system and increased mortality [40,61]. Meta-analyses of randomized studies suggest that glutamine and antioxidant supplementation in critically ill patients may be associated with prolonged survival [62,63].…”
Section: Immunomodulatory Nutritionmentioning
confidence: 99%
“…However, in a recent study with intensive care unit (ICU) patients, it has been encountered that TPN supplemented with glutamine dipeptide is safe, but does not alter clinical outcomes among the patients [302], while clinical trials have not demonstrated prolonged advantages, such as reductions in mortality or risk of infections in adults [303]. In a recent meta-analysis of randomized clinical trials [304], no difference has been found to allow the recommendation of glutamine supplementation to generic population of critically ills. Therefore, the efficacy of glutamine supplementation is still under debate.…”
Section: Physical Exercise Glutamine and Hs Response In Agingmentioning
confidence: 99%